2008
DOI: 10.2166/wst.2008.835
|View full text |Cite
|
Sign up to set email alerts
|

Settling velocity of particulate pollutants from combined sewer wet weather discharges

Abstract: Settling velocities of TSS and of particulate pollutants (COP, PDCO, PTKN, PCu, PPb, PZn, PPAH) measured on a wide range of wet weather flow (WWF) samples collected at different levels of the Parisian combined sewer system are reported. The recorded V30 (0.01 to 0.1 mm s(-1)) and V50 (0.09 to 0.6 mm s(-1)) values exceed by a factor 10 those of dry weather sewage and also exceed the values measured for pavement runoff. These values lie however often below the 0.28 mm s(-1) reference value considered in France f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In our case, it has been estimated from measurements made in streams using fine organic particles marked by a tracer (Minshall et al, 2000;Thomas et al, 2001) and on laboratory measurements. The average settling velocity suggested corresponds to measurements conducted on the River Seine after a CSO discharge (Even et al, 2004) and is in accordance with settling velocities observed using the French VICAS protocol (Gromaire-Mertz et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…In our case, it has been estimated from measurements made in streams using fine organic particles marked by a tracer (Minshall et al, 2000;Thomas et al, 2001) and on laboratory measurements. The average settling velocity suggested corresponds to measurements conducted on the River Seine after a CSO discharge (Even et al, 2004) and is in accordance with settling velocities observed using the French VICAS protocol (Gromaire-Mertz et al, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…After a thorough literature review, two methods were combined to determine the settling behavior of the collected samples. The experimental setup follows the VICPOL protocol [8]. The process itself is simple and the experimental conditions are comparable to real world conditions in stagnant pressure tubes.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…For the subsequent data processing, the related VICAS protocol [23] was applied to describe the distribution of settling velocities in the sample as continuous mathematical function. Figure 1 shows a schematic view (similar to [8]) and a photo of the construction. The VICPOL protocol determines n mass fractions with their specific settling velocity v s (mm/s), by dividing the sewage sample into n sub-samples with n settling times.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations